The Influence of Organizational Culture and Job Satisfaction on Organizational Commitment in Employees (Case Study: Education and Training Center for Supervision of the Financial and Development Supervisory Agency) - Ismartaya; Endang Silaningsih; Nuria Fitri Ramadani (International Journal of Educational and Life Sciences, 2024)
This research was conducted to determine the partial and simultaneous influence of organizational culture and job satisfaction on organizational commitment. The sample used in this research was 134 BPKP Pusdiklatwas employees using a simple random sampling technique. The research method used was multiple linear regression and obtained results 1) organizational culture has a partially positive and significant effect on organizational commitment; 2) job satisfaction does not have a positive and partially significant effect on organizational commitment; 3) organizational culture and job satisfaction simultaneously have a positive and significant effect on organizational commitment.